A valveless micropump based on additive fabrication technology. (24th May 2019) - Nhu, Cuong Nguyen; Van, Luan Le; Ngoc, An Nguyen; Dau, Van Thanh; Bui, Tung Thanh; Duc, Trinh Chu
A valveless microfluidic pump fabricated by additive fabrication technology is presented. Nozzle/diffuser structures are used to direct the flow of liquid currents inside the PZT-based micropump. A unique design using the collision of two inlet currents helps reduce the back-flow during the suction phase and promotes mixing ability. The micropump is simulated and a positive flow rate is observed at the outlet. The performance of the pump is further investigated at different driving frequencies and voltages. Simulation study on the nozzle/diffuser helps determine an efficient configuration of the nozzle/diffuser of 6° opening angle. The proposed micropump is suitable for low-cost disposable applications and is capable of delivering a controlled amount of liquid.